Implementas Nilai-Nilai Pendidikan Berkarakter melalui Pembelajaran Sejarah - Nisa Ulaini (Tarikhuna: Journal of History and History Education, 2023)
The research is motivated by the lack of interest of students in learning history so that they are unable to take the wisdom values from the past in improving the character of the students themselves. Evidenced by the fact that there are still students who have low character such as skipping classes, smoking, not being disciplined about time, not respecting teachers and so on. The research method used is qualitative research. Data sources are school principals, history teachers and class XI students. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis with data reduction, data presentation, and draw conclusions. Based on the result of field research, it shows that the history teacher’s readiness in implementing character education is good by preparing the syllabus and lesson plan, the implementation of character education assessment instruments, but it is done well because it is in accordance with the syllabus and lesson plan inserted with a value assessment the value of the nation’s character. Student’s perceptions or responses to the implementation of character education are good, as evidenced by good character according to what students say that the instilling of character according to what students say that the instilling of character according to what students say that the instilling of character values by teachers is good, but some students do not instill character education in their lives so that there are still students who violate teacher rules. Constraints experienced by teachers, namely a very short time, a conducive social environment, and electronic media